Venous cannulation and topical ethyl chloride in patients receiving nitrous oxide. - Crecelius, C. (American Dental Society of Anesthesiology, 1999)
The purpose of this study was to evaluate the effect of ethyl chloride spray on the anxiety and pain associated with placing an intravenous catheter in patients sedated with nitrous oxide. Eighty-eight patients scheduled for dental surgery with a combination of intravenous and nitrous oxide sedation were randomly assigned to have ethyl chloride spray or a placebo, water spray, applied before cannulation of a vein. Anxiety and pain were reported using a 10.0-cm visual analog scale before nitrous oxide administration, after nitrous oxide sedation, following application of the spray, and following venous cannulation. The first 2 assessments measured overall levels of patient anxiety and pain and confirmed that nitrous oxide sedation reduced anxiety without changing already low levels of pain. The second 2 assessments of anxiety and pain measured the reaction toward the spray and cannulation. The application of ethyl chloride spray produced significantly more anxiety and pain than did the placebo. The results of this study demonstrate that ethyl chloride spray does not significantly reduce the anxiety and pain associated with venous cannulation in patients sedated with nitrous oxide.